2021
DOI: 10.2147/cmar.s272116
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Serum D-Dimer for Detection of Gallbladder Carcinoma

Abstract: Background: Previous studies have shown that D-dimer plays an essential role in the occurrence and development of various tumors, and its diagnostic value in gallbladder carcinoma (GBC) is unknown. Therefore, the purpose of our study was to explore the diagnostic value of D-dimer in distinguishing between gallbladder carcinoma and benign controls. Methods: We retrospectively included age and gender-matched patients with gallbladder carcinoma and benign gallbladder lesions, and analyzed the diagnostic value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Inappropriate activation of both coagulation and fibrinolysis is usually discovered in carcinoma patients, especially in those with metastatic disease (17)(18)(19)(20). Plasma D-dimer, the smallest cross-linked protein produced in the proteolytic process, is a marker for detecting malignancy and is of great significance for the clinical exclusion of tumor-related thrombosis (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inappropriate activation of both coagulation and fibrinolysis is usually discovered in carcinoma patients, especially in those with metastatic disease (17)(18)(19)(20). Plasma D-dimer, the smallest cross-linked protein produced in the proteolytic process, is a marker for detecting malignancy and is of great significance for the clinical exclusion of tumor-related thrombosis (21).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma D-dimer, the smallest cross-linked protein produced in the proteolytic process, is a marker for detecting malignancy and is of great significance for the clinical exclusion of tumor-related thrombosis (21). Previous studies have shown the predictive role of plasma D-dimer in many malignancies treated with chemotherapy, including lung cancer (22)(23)(24)(25)(26), colorectal cancer (27), gallbladder carcinoma (20), and breast cancer (28). However, whether pretreatment D-dimer can predict therapeutic efficacy and prognosis in advanced NSCLC patients receiving ICI treatment remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of coagulation disorder in the diagnosis of some malignant tumors has also been reported. For example, APTT and platelet distribution width (PDW used individually or in combination showed good predictive values for nasopharyngeal carcinoma, while APTT, FIB, and DD2 were significantly associated with nasopharyngeal carcinoma metastasis [ 25 ]; there was an independent correlation between abnormally increased FIB and prostate cancer sensitivity [ 26 ]; serum DD2 was a potential marker for the diagnosis of gallbladder cancer, and DD2 combined with CA199 had excellent diagnostic value for this cancer (AUC = 0.920) [ 27 ]. As in other malignant tumors, some CC parameters have been reported to have diagnostic value for PC.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The correlation between PLR, NLR, and D-dimer (D-D) and the prognosis of solid tumors has been confirmed, such as for gastric carcinoma, colorectal neoplasms, liver tumors, breast carcinoma and bile duct carcinoma. [7][8][9] In recent years, studies have found that use of inflammation-related prognostic indicators and blood coagulation fibrinolysis system markers (D-D) can predict the survival and prognosis of patients with esophageal carcinoma, colorectal carcinoma, gastric carcinoma, ovarian carcinoma and NSCLC. [10][11][12] However, whether D-D before treatment and combined PLR and NLR can predict the shortterm efficacy and prognosis of SCLC sufferers is unclear.…”
Section: Introductionmentioning
confidence: 99%